Дія кримінального права : динамічні аспекти - Туляков, Вячеслав Олексійович; Туляков, Вячеслав Алексеевич; Tuliakov, Viacheslav O.; Туляков, В. О. (My University, 2012)
The article is devoted to criminal law dynamic model on different levels of social interaction. It is stressed that criminal law dynamics should be analyzed as one of the primary characteristics of modern criminal law theory.
Туляков В. О. Дія кримінального права : динамічні аспекти / В. О. Туляков // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 389-394.
Keywords: кримінальне право; динаміка права; буття права; уголовное право; динамика права; бытие права; criminal law; law dynamics; law existence